2D black arsenic phosphorus and its application for anodes of lithium ion batteries. Issue 47 (16th November 2020) - Hou, Yanyan; Ma, Shufang; Liu, Qingming; Zhang, Shuai; Chu, Yangyang; Hao, Xiaodong; Han, Bin; Xu, Bingshe
Abstract : Two-dimensional (2D) structured black arsenic phosphorus (B-AsP) compound materials play a pivotal role in a wide range of applications due to their exotic physical properties and flexible architectures. Abstract : Two-dimensional (2D) structured black arsenic phosphorus (B-AsP) compound materials play a pivotal role in a wide range of applications due to their exotic physical properties and flexible architectures. Here, 2D B-AsP compound materials were synthesized via mineralization-assisted gas phase transport. High-resolution X-ray diffraction (HRXRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) were used to characterize the composition and crystal structures of the B-AsP flakes. The results show that the synthesized B-AsP has good crystallinity and composition close to the designed value. B-AsP compound materials are new materials with a high theoretical specific capacity and can be used as negative electrodes in lithium ion batteries (LIBs). These materials show a higher specific capacity in their first charge/discharge cycle than graphite. These data provide basic support for research on the energy storage capacity of B-AsP compound materials. The results have great potential for improving the performance of lithium ion batteries.